Rob Poulton with Brian Hope-Taylor, A Norman Chapel and a Later 12th and 13th Century Manorial Enclosure at Preston Hawe, Tadworth, Surrey - Christie, Neil (Medieval Settlement Research, 2024)
Book review of A Norman Chapel and a Later 12th and 13th Century Manorial Enclosure at Preston Hawe, Tadworth, Surrey.